Preparation of Ultrafine Spherical Al-Mg Alloy and Its Energy Release Characteristics in Explosives - Junhui Liu; Jie Yao; Zichao Wang; Wei Liu; Jianxin Nie; Shi Yan (Metals)
The substitution of aluminum powder with highly reactive ultrafine aluminum-based metal fuels has a significant impact on the energy release of aluminum-containing energetic materials because of their excellent energy density and combustion performances. A series of ultrafine spherical Al-Mg alloy fuels with different contents of magnesium were prepared by close-coupled gas atomization technology. The properties of Al-Mg alloy powders of 13~15 μm were tested by SEM, TG-DSC, and laser ignition experiments. Results show that alloying with magnesium can significantly enhance thermal oxidation and combustion performance, leading to more oxidation weight gains and higher combustion heat release. HMX-based castable explosives with the same content of Al and the novel Al-Mg alloy were made and tested. Results show that the detonation performances of HMX/Al-Mg alloy/HTPB are better than HMX/Al/HTPB. Compared to the HMX/Al/HTPB explosive, the detonation heat of HMX/ Al-Mg alloy/HTPB was increased by 200 kJ/kg, the energy release efficiency was enhanced from 80.55% to 83.19%, the detonation velocity was increased by 114 m/s, and the shock wave overpressure at 5 m was increased by 83%. This research provides a new type of composite metal fuel for improving the combustion performance of Al powder.